2021
DOI: 10.1136/bmjgast-2021-000648
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene glycol versus lactulose in the treatment of hepatic encephalopathy: a systematic review and meta-analysis

Abstract: BackgroundHepatic encephalopathy (HE) is defined as brain dysfunction that occurs because of acute liver failure or liver cirrhosis and is associated with significant morbidity and mortality. Lactulose is the standard of care till this date; however, polyethylene glycol (PEG) has gained the attention of multiple investigators.MethodsWe screened five databases namely PubMed, Scopus, Web of Science, Cochrane Library and Embase from inception to 10 February 2021. Dichotomous and continuous data were analysed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
3
5
1
1
Order By: Relevance
“…Reason for this difference is that alcohol consumption is almost negligible in our society. Improvement in grade of encephalopathy in 24 hours after treatment with PEG was seen in our study and this was consistent with Hoila et al [25]. [28] in which hospital stay was 4±1 days of hospitalisation in PEG group versus 8±2 days of hospitalisation in lactulose group.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Reason for this difference is that alcohol consumption is almost negligible in our society. Improvement in grade of encephalopathy in 24 hours after treatment with PEG was seen in our study and this was consistent with Hoila et al [25]. [28] in which hospital stay was 4±1 days of hospitalisation in PEG group versus 8±2 days of hospitalisation in lactulose group.…”
Section: Discussionsupporting
confidence: 92%
“…Attar A. et al demonstrates that PEG electrolyte solution is more powerful laxative than lactulose [24]. Our study demonstrates that PEG 3350 electrolyte solution is more effective than lactulose in improvement of hepatic encephalopathy with mean drop in HESA score by 1.37 in PEG group as compared to only 0.65 drop in lactulose group at 24 hours of treatment, the results being consistent with the study conducted by Hoila et al [25].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Recent results published in a systematic review and meta-analysis demonstrated higher drops in the HE Scoring Algorithm (HESA) score and thus faster resolution of HE when compared with lactulose alone. 21 Neomycin and metronidazole are mentioned in the American Association for the Study of Liver Diseases/European Association for the Study of the Liver (AASLD/EASL) practice guidelines as alternative agents, but, based on unfavorable safety profiles, are not routinely recommended. 6,22 Vancomycin has fallen out of favor and is no longer recommended as a treatment option due to limited studies, high cost, and increased prevalence of drug resistance associated with its use.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PEG applicability may be limited to patients in whom naso-gastric tube placement is safe and successful. A recent review and meta-analysis of four studies [20] showed that a single dose of PEG significantly improved clinical features of HE after 24 h and reduced the number of days for HE resolution compared to lactulose; however, no differences were observed in hospitalization length.…”
Section: Polyethylene Glycol (Peg)mentioning
confidence: 99%